Perbandingan Penerapan Metode Brainstorming dan Buzz Group Terhadap Peningkatan Pengetahuan Suami Ibu Hamil Tentang Tanda Bahaya Kehamilan, Persalinan, Dan Nifas (Studi Kasus Di Bogor) - Winancy Winancy; Ardini S. Raksanagara; Yoni Fuadah (AIPKIND (Asosiasi Pendidikan Kebidanan Indonesia), 2015)
It is important to give the husbands of pregnant women, as decision makers in the family, health education about the danger signs in pregnancy, childbirth, and postpartum. Methods of brainstorming and buzz group on health education are able to stimulate the active role of participants of a discussion, so they accept the information given to them more easily. This was a Quasi Experimental Study with Non Randomized Pretest-Posttest design. Population in this study consisted of the husbands whose wife was pregnant and lived in the work area of Sukamakmur Puskesmas (Community Health Center) in Bogor District. Accidental sampling method was used and it involved two groups, namely brainstorming group consisting of 63 respondents and buzz group consisting of 61 respondents. Statistical analysis used Wilcoxon and Mann-Whitney tests. The results showed that the respondents knowledge was improved immediately after the health education had been given (p <0.001). The results of Mann-Whitney test described that the increased median value of knowledge of the respondents in buzz group was better than that in brainstorming group. The conclusion shows that Buzz group has better impacts on the increased median value of the respondents’ knowledge.